A Biblical Aramaic reader : with an outline grammar - Muraoka, T. (Peeters, 2020)
This reader is for anyone very eager to read the story of Daniel in the lions' den and many other fascinating stories in their original language, Aramaic. A brief outline of Biblical Aramaic grammar is followed by a verse-to-verse grammatical commentary on the Aramaic chapters in the books of Daniel and Ezra. Both the outline grammar and the grammatical commentary presuppose basic knowledge of the grammar and vocabulary of Biblical Hebrew. Constant references are made in the commentary to relevant sections of the outline grammar. The commentary is written in a user-friendly, not overtly technical language. Some grammatical exercises with keys and paradigms conclude the Reader.